2022
DOI: 10.3390/diagnostics12102279
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Self-Collected Nasal and Oral Swabs for Detection of SARS-CoV-2

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the third highly pathogenic human coronavirus and is rapidly transmitted by infected individuals regardless of their symptoms. During the COVID-19 pandemic, owing to the dearth of skilled healthcare workers (HCWs) to collect samples for early diagnosis, self-collection emerged as a viable alternative. To evaluate the reliability of self-collection, we compared the virus detection rate using 3990 self-collected swabs and HCW-collected swabs, procur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Most of the research on self-testing actually assessed self-sampling and not the complete self-testing process. Such studies indicated that high quality samples can be taken by users, with self-taken samples tested against PCR yielding sensitivities and specificities close to, or above the WHO's target product profile recommended sensitivity and specificity thresholds of 80% and 97% (19)(20)(21)(22)(23)(24)(26)(27)(28). Regarding the complete self-testing process (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the research on self-testing actually assessed self-sampling and not the complete self-testing process. Such studies indicated that high quality samples can be taken by users, with self-taken samples tested against PCR yielding sensitivities and specificities close to, or above the WHO's target product profile recommended sensitivity and specificity thresholds of 80% and 97% (19)(20)(21)(22)(23)(24)(26)(27)(28). Regarding the complete self-testing process (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, when participants were observed in Zambia, a considerable number of participants had difficulties following some of the steps correctly. Some of these difficulties such as removing the swab from the tube and extracting the liquid from the swab were also observed to be difficult for participants in the study in Malawi and Zimbabwe assessing usability of the same tests [23]. The study population in Malawi and Zimbabwe included health workers, who can be expected to be familiar with the testing process and able to understand instruction and to self-test easily compared to other populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal cycling conditions were as follows: 50 °C for 20 min; 95 °C for 15 min; and 45 cycles at 95 °C for 10 s, 60 °C for 15 s, and 72 °C for 10 s. The data were analyzed using Seegene Viewer (v3.24; Seegene Inc.). The results were interpreted as SARS-CoV-2 positive when the Ct value was ≤40 for all targets, according to the manufacturer’s instructions [ 9 ]. Of these, RdRP and S were represented by a Ct value from rRT-PCR in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The rRT-PCR assay is the gold-standard test for SARS-CoV-2 detection, especially when using nasopharyngeal swabs (NPSs) obtained from suspected cases by trained healthcare workers [ 9 ]. However, rRT-PCR assays have a turnaround time of approximately 24–48 h, which results in a bottleneck in PCR testing during the peak period of SARS-CoV-2 infections, which adversely affects the management of patients with COVID-19 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%